The Relationship Parents’ Attention and the Interest of Community Learning in Nagari Koto Taratak Sutera Sub-District Pesisir Selatan - Yova Andre; Vevi Sunarti (Universitas Negeri Padang, 2020)
This research is motivated by a phenomenon that occurs in Nagari Koto Taratak, Sutera District, Pesisir Selatan, namely the low interest in learning from the community. This is evidenced by the large number of students who have dropped out of school, both formal and non-formal education. The cause of the low interest in learning in the community is thought to be due to parents who do not pay enough attention, then it has a negative impact on the development of their education. Therefore, the purpose of this study is to describe the attention of parents, describe the interest in community learning and the significant relationship between parents' attention and community learning interest in Kenagarian Koto Taratak, Sutera District, Pesisir Selatan. This type of research is correlational quantitative. The population in this study were people who dropped out of school in Kenagarian Koto Taratak, Sutera District, Pesisir Selatan. The sampling technique in this study was cluster random sampling. The data collection technique is a questionnaire. The data collection tool is a list of statements. The data analysis technique used the percentage formula and rho spearman. The results of this study are low parental attention, low community interest in learning and there is a significant relationship between parental attention and community learning interest in Kenagarian Koto Taratak, Sutera District, Pesisir Selatan Regency. Suggestions in this study are expected that parents pay more attention to children's learning activities because high attention is needed by children in the learning process so that children's learning interests will grow well, it is hoped that parents can create good relationships with children to communicate children's learning activities at school. So that parents can continue to provide motivational encouragement, meet student learning needs, and find out about children's learning progress.Keywords: parental attention, interest in learning